Magnetically recyclable catalytic carbon nanoreactors - Aygün, Mehtap; Chamberlain, Thomas W.; Gimenez-Lopez, Maria del Carmen; Khlobystov, Andrei N. (Wiley, 2018)
Multifunctional nanoreactors are assembled using hollow graphitized carbon nanofibers (GNFs) combined with nanocatalysts (Pd or Pt) and magnetic nanoparticles. The latter are introduced in the form of carbon‐coated cobalt nanomagnets (Co@Cn) adsorbed on GNF, or formed directly on GNF from ferrocene yielding carbon‐coated iron nanomagnets (Fe@Cn). High‐resolution transmission electron microscopy demonstrates that Co@Cn and Fe@Cn are attached effectively to the GNFs, and the loading of nanomagnets required for separation of the nanoreactors from the solution with an external magnetic field is determined using UV–vis spectroscopy. Magnetically functionalized GNFs combined with palladium or platinum nanoparticles result in catalytically active magnetically separable nanoreactors. Applied to the reduction of nitrobenzene the multifunctional nanoreactors demonstrate high activity and excellent durability, while their magnetic recovery enables significant improvement in the reuse of the nanocatalyst over five reaction cycles (catalyst loss < 0.5 wt%) as compared to the catalyst recovery by filtration (catalyst loss)